2010
DOI: 10.1007/s10295-010-0839-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in stationary-phase cells of a commercial Saccharomyces cerevisiae wine yeast grown in aerobic and microaerophilic batch cultures assessed by electric particle analysis, light diffraction and flow cytometry

Abstract: We applied electric particle analysis, light diffraction and flow cytometry to obtain information on the morphological changes during the stationary phase of Saccharomyces cerevisiae. The reported analyses of S. cerevisiae populations were obtained under two different conditions, aerobic and microaerophilic, at 27°C. The samples analysed were taken at between 20 and 50 h from the beginning of culture. To assist in the interpretation of the observed distributions a complexity index was used. The aerobically gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…En ellos, las condiciones del entorno varían y Saccharomyces debe adaptarse a los cambios ambientales viéndose obligada a pasar en poco tiempo de condiciones aerobias a microaerófilas y a anaerobias, cambiando el tipo de metabolismo en relación a la concentración de oxígeno presente. Comprender su crecimiento respirofermentativo es importante para optimizar los diferentes procesos biotecnológicos en los que esta levadura está implicada (Portell, Ginovart, Carbó & Vives-Rego, 2011;Carbó et al, 2015).…”
Section: La Levadura Saccharomyces Cerevisiaeunclassified
“…En ellos, las condiciones del entorno varían y Saccharomyces debe adaptarse a los cambios ambientales viéndose obligada a pasar en poco tiempo de condiciones aerobias a microaerófilas y a anaerobias, cambiando el tipo de metabolismo en relación a la concentración de oxígeno presente. Comprender su crecimiento respirofermentativo es importante para optimizar los diferentes procesos biotecnológicos en los que esta levadura está implicada (Portell, Ginovart, Carbó & Vives-Rego, 2011;Carbó et al, 2015).…”
Section: La Levadura Saccharomyces Cerevisiaeunclassified
“…In addition, the morphology of the cells is closely related to their physiological state and their status in the cell cycle (Coelho et al, 2004 ). The relevance of cell size measurements to study the response of yeast cells submitted to various stresses has also been shown (Tibayrenc et al, 2010 ; Portell et al, 2011 ).…”
Section: Introductionmentioning
confidence: 95%
“…Both measures combine equilibrium (disorder) and disequilibrium (order) parameters resulting in expressions for complexity. Several problems were successfully studied with this approach as, for instance, in Biology [11,12] and Meteorology [13], but with criticism concerning the same weight to order and disorder.…”
Section: Introductionmentioning
confidence: 99%